2008
DOI: 10.1063/1.2987719
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of very-high-spin organic π-conjugated polymers based on Green’s function theory

Abstract: Magnetic properties of two very-high-spin organic pi-conjugated polymers have been investigated theoretically by means of the many-body Green's function method with random phase approximation. The polymers are designed with a large density of cross-links and alternating connectivity of radical modules with unequal spin quantum numbers (S), macrocyclic S=2 or 3, and cross-linking S=1/2 modules, which permit large net S values for either antiferromagnetic or ferromagnetic exchange coupling between the modules. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Relevant work has been carried out by several groups [11][12][13][14][15][16][17][18][19][20][21]. In our latest study on the MFEs in pure Alq 3 based OLEDs [22], we found that the MEL shows a sharp increase at low fields and followed by a significant decrease at high fields more than about 40 mT at low temperature (T≤150 K) and large injection current.…”
Section: Dye Doping Magnetic Field Dependent Of Electroluminescencementioning
confidence: 90%
See 1 more Smart Citation
“…Relevant work has been carried out by several groups [11][12][13][14][15][16][17][18][19][20][21]. In our latest study on the MFEs in pure Alq 3 based OLEDs [22], we found that the MEL shows a sharp increase at low fields and followed by a significant decrease at high fields more than about 40 mT at low temperature (T≤150 K) and large injection current.…”
Section: Dye Doping Magnetic Field Dependent Of Electroluminescencementioning
confidence: 90%
“…Several possible models have been proposed to explain these MFEs, such as Bipolaron mechanism [8], exciton-charge reaction mechanism [9], triplet-triplet annihilation process (TTA S*) → [10] and magnetic field modulated hyperfine interaction [11]. Relevant work has been carried out by several groups [11][12][13][14][15][16][17][18][19][20][21]. In our latest study on the MFEs in pure Alq 3 based OLEDs [22], we found that the MEL shows a sharp increase at low fields and followed by a significant decrease at high fields more than about 40 mT at low temperature (T≤150 K) and large injection current.…”
mentioning
confidence: 98%
“…The spin-dependent currents in the above-mentioned two-probe devices based on P- and As-adsorbed AsP monolayers are calculated by DFT combined with the standard nonequilibrium Green's function. 41–45 Considering that the temperature gradient (Δ T ) between two electrodes is applied to drive the carriers to transport, the thermally-driven spin-dependent current I ↑(↓) can be given by 46,47 where the upward (downward) arrow of I ↑(↓) represents the spin-up (spin-down). h and e refer to the Plank's constant and the electron charge, respectively.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…, ; e d t t i [47,48] (6), the average force on the n-th GC pair depends on the electron population, changing with the applied bias.…”
Section: Model and Methodsmentioning
confidence: 99%